2016
DOI: 10.1111/ibi.12373
|View full text |Cite
|
Sign up to set email alerts
|

Extremes of heat, drought and precipitation depress reproductive performance in shortgrass prairie passerines

Abstract: Climate change elevates conservation concerns worldwide because it is likely to exacerbate many identified threats to animal populations. In recent decades, grassland birds have declined faster than other North American bird species, a loss thought to be due to habitat loss and fragmentation and changing agricultural practices. Climate change poses additional threats of unknown magnitude to these already declining populations. We examined how seasonal and daily weather conditions over 10 years influenced nest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 60 publications
2
71
2
Order By: Relevance
“…Thus, extreme precipitation events frequently lower nesting success in both high-elevation (e.g., Hendricks andNorment 1991, Decker andConway 2009, present study) and low-elevation environments (Fisher et al 2015, Conrey et al 2016. Open-country birds breeding in warmer environments at lower elevations and latitudes are also susceptible to hot weather over short periods and drought conditions over longer periods (George et al 1992, Bolger et al 2005.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Thus, extreme precipitation events frequently lower nesting success in both high-elevation (e.g., Hendricks andNorment 1991, Decker andConway 2009, present study) and low-elevation environments (Fisher et al 2015, Conrey et al 2016. Open-country birds breeding in warmer environments at lower elevations and latitudes are also susceptible to hot weather over short periods and drought conditions over longer periods (George et al 1992, Bolger et al 2005.…”
Section: Discussionmentioning
confidence: 53%
“…In temperate biomes, parent birds must make up a thermal deficit or excess of 10-408C or more from ambient conditions by heating and cooling their offspring over a period of several weeks while meeting their own somatic requirements (Conway and Martin 2000a, 2000b. Although cold or inhospitable weather is considered to be an energetic challenge with potential fitness costs (Hendricks and Norment 1991, Martin and Wiebe 2004, 2006, the difference in the ecological costs to birds breeding in normal vs. extreme weather conditions has received little study until recently (Skagen and Yackel Adams 2012, Pipoly et al 2013, Conrey et al 2016. In general, we have little direct knowledge as to which elements of ambient weather constitute ''extreme conditions'' for bird species within or across habitats, which has hampered our ability to refine predictions about the impacts of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…In northern Colorado (U.S.A.), hot (≥35°C) or stormy days and drier breeding conditions are associated with lower nest survival for grassland birds (Conrey et al. ). Conversely, years with warmer and wetter conditions promote elevated reproductive success for grassland birds, suggesting indirect benefits of increased grassland productivity (Rotenberry & Wiens ; Chase et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the decrease in density by Western Meadowlark across both bison and reference sites can probably be attributed to fluctuations in precipitation during our study period (Niemuth et al, 2008). Other studies have demonstrated decreases in nest survival for shortgrass prairie birds during periods of drought or increased temperatures (Conrey, Skagen, Yackel Adams, & Panjabi, 2016). Other studies have demonstrated decreases in nest survival for shortgrass prairie birds during periods of drought or increased temperatures (Conrey, Skagen, Yackel Adams, & Panjabi, 2016).…”
Section: Discussionmentioning
confidence: 63%